Innowacyjność jako element kapitału ludzkiego kadr samorządowych województwa podkarpackiego - Tuziak, Arkadiusz; Tuziak, Bożena (MITEL, 2005)
Artykuł podejmuje problematykę szeroko rozumianej zdolności innowacyjnej przedstawicieli władz samorządowych. Zdolność innowacyjna, stanowiąca istotny element kapitału ludzkiego, została sformułowana zarówno w wymiarze indywidualnym, jak i instytucjonalnym. W artykule przedstawiono złożone uwarunkowania postaw innowacyjnych oraz różne obszary działalności innowacyjnej administracji samorządowej, określające jej poziom otwartości na zmiany i gotowość w zakresie twórczej adaptacji do współczesnych wyzwań rozwojowych. Podstawą analiz zawartych w artykule są wyniki badań empirycznych (przedstawionych w formie syntetycznej) przeprowadzonych w ramach realizacji projektu celowego Ministerstwa Edukacji i Informatyki Wdrożenie Nr 6 RSI2003C/5997 „Regionalne Strategia Innowacji Województwa Podkarpackiego.

The article undertakes problems of a widely understood innovation ability of representatives of local self-government authorities. The innovation ability, constituting an essential element of human capital, was formulated both in an individual and institutional dimension. The article presents complex conditions of innovative attitudes and various areas of innovation activities of self-government administration determining its level of openness to changes and readiness in the scope of creative adaptation to contemporary developmental challenges. A basis of analyses contained in the article are results of the empirical research (presented in a synthetic form) carried out in the scope of realisation of the target project of the Ministry of Education and Computer Science Implementation No. 6 RSI2003C/5997 “Regional Strategy of Innovation of the Podkarpackie Province.
Innovation Ability as an Element of Human Capital of Self-Government Personnel of the Podkarpackie Province